PENGGUNAAN TEKNOLOGI DAN GAYA BELAJAR SISWA PADA PEMBELAJARAN PAI - Romdana, Dede; Fadhilah, Nurul; Aisyah, Ati Rahmawati; Mutaqin, Mumu Zainal (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
This research aims to find out about the use of information and communication technology (ICT) in Islamic Religious Education (PAI) learning with a focus on its influence on student learning styles. Through library research methods, this research analyzes various literature sources that discuss ICT in PAI education and its influence on student learning styles. The research results show that ICT has great potential to improve the quality and relevance of PAI learning, especially in terms of accessibility, efficiency and interactivity.  ICT can facilitate access to quality learning resources, such as literature, journals and learning videos. In addition, ICT can help teachers manage administration and learning materials, thereby increasing efficiency. The use of ICT can also create more interactive and interesting learning for students, such as through simulations, educational games and online learning platforms. Research also highlights the importance of understanding students' learning styles in optimizing the use of ICT. By understanding students' learning styles, teachers can choose and implement learning strategies that are more effective and appropriate to students' needs.  Every student has different learning preferences, such as visual, auditory, and kinesthetic.  By understanding students' learning styles, teachers can choose appropriate learning methods, make optimal use of ICT, and create a more effective and enjoyable learning environment. This research concludes that the use of ICT in PAI learning needs to be integrated with an understanding of student learning styles to achieve optimal learning outcomes.